2011
DOI: 10.3748/wjg.v17.i39.4404
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of restless legs syndrome in patients with irritable bowel syndrome

Abstract: Restless legs syndrome is prevalent in patients with IBS, especially those with diarrheal symptoms. Assessment of concomitant disorders may improve diagnosis and expand relevant treatment options for patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
1
9
1
Order By: Relevance
“…Our findings of IBS patients with co-morbid RLS revealed they suffered more from stomach pain, nausea and vomiting. Although, not statistically significant, the highest prevalence of RLS was reported in IBS-M (28.1%) and IBS-C (26.7%) patients, respectively, which was not in line with Basu's report 21. Even though SIBO is not evaluated in our study, this difference between Basu's findings21 and our investigation may reflect different portion of SIBO subtypes such as hydrogen-producer or methane-producer; where methane-producer has been reported to be more associated with constipation 22…”
Section: Discussioncontrasting
confidence: 75%
“…Our findings of IBS patients with co-morbid RLS revealed they suffered more from stomach pain, nausea and vomiting. Although, not statistically significant, the highest prevalence of RLS was reported in IBS-M (28.1%) and IBS-C (26.7%) patients, respectively, which was not in line with Basu's report 21. Even though SIBO is not evaluated in our study, this difference between Basu's findings21 and our investigation may reflect different portion of SIBO subtypes such as hydrogen-producer or methane-producer; where methane-producer has been reported to be more associated with constipation 22…”
Section: Discussioncontrasting
confidence: 75%
“…Such a sensorimotor disorder is called restless legs syndrome and it affects from 1 to 10 percent of the population [21]. Interestingly, it was found that restless legs syndrome prevails in patients with intestinal disorders [22].…”
Section: The Visceral Theory Of Sleepmentioning
confidence: 99%
“…Moreover, changes in the small intestinal bacterial overgrowth (SIBO)-related inflammatory mediator impaired communication between enteric and central nervous system are reported as the pathogenetic mechanisms [5]. A couple of studies have suggested that sleep disorders, particularly restless legs syndrome (RLS), are possible comorbidities in IBS patients [6, 7]. According to the previous studies, nearly 25%–30% of IBS patients experience RLS [68].…”
Section: Introductionmentioning
confidence: 99%